Review of transcutaneous electrical acupoint stimulation and related devices - Lei Wang; Xinjiang Zhang; Bowen Feng; Shuai Zhang; Yanfeng Zheng; Chen Xin; Chong Su; Fang Wang; Mozheng Wu; Jinling Zhang; Yuqi Liu; Liang Li; et al. (Science of Traditional Chinese Medicine)
Abstract. A review was undertaken of the operation process and development of transcutaneous electrical acupoint stimulation (TEAS) and related devices for TEAS, with the aim to offer a reference for developing an international standard for the basic safety and essential performance of the devices. The articles related to TEAS and instruction of devices for TEAS were searched using the EMBASE, MEDLINE, and Web of Science databases with the time period from inception to July 18, 2023. In the absence of a parameter description of the stimulators, a multimeter was used to measure the output voltage, resistance, and current. Thirty-two related devices for TEAS were obtained. The safety parameters of most devices were neither clearly defined, nor standardized, and in some cases were missing. There was a noticeable disparity in the upper safety limits of the output current among the devices. The sizes of the skin electrode pads as well as the lengths of the electrode connecting wires of most devices were not clearly indicated. Acupoints on different parts of the human body, including the upper limbs, head, auricle, chest, abdomen, trunk, and lower limbs, required different maximum tolerable current intensities and current densities. It is important to indicate comprehensive output/safety parameters and essential performance for devices for TEAS to meet the need of global distribution, achieve precise stimulation parameters at different acupoints across the human body, and allay any safety concern of national therapeutic device authorities, the regulators, manufacturers, and end users.